Psychometric Evaluation of the Adherence in Diabetes Questionnaire - Kristensen, Lene J. (American Diabetes Association, 2012)
OBJECTIVE: To assess the psychometric properties of a short, new, self-administered questionnaire (17–19 items) for evaluating the adherence behavior of children and adolescents with type 1 diabetes and their caregivers. This instrument has separate versions depending on the means of insulin administration, i.e., continuous subcutaneous insulin infusion (Adherence in Diabetes Questionnaire [ADQ]-I), or conventional insulin injection (ADQ-C). RESEARCH DESIGN AND METHODS: A total of 1,028 caregivers and 766 children and adolescents 2–17 years of age were recruited through the Danish Registry of Childhood Diabetes and completed the national web survey, including the ADQ and psychosocial measures of self-efficacy, parental support, family conflict, and aspects of diabetes-related quality of life. Blood samples were obtained for central HbA(1c) analysis. The psychometric properties of the ADQ were evaluated, and the association with glycemic control was assessed. RESULTS: There was good internal consistency for both the youth and caregiver reports and strong agreement between the caregiver and youth reports. Higher ADQ scores, indicating better adherence, were associated with better self-efficacy, more parental support, less diabetes-related conflict, and less experience with treatment barriers. Factor analysis supported maintaining the one-factor structure of the ADQ. Higher ADQ scores were associated with lower HbA(1c) levels. CONCLUSIONS: The ADQ showed good psychometric properties. Although the test-retest reliability and sensitivity to change of the instrument still need to be established, the ADQ appears to be a valuable tool for assessing adherence in families with children and adolescents with type 1 diabetes in both clinical and research settings.